The Combination of MK-2206 and WZB117 Exerts a Synergistic Cytotoxic Effect Against Breast Cancer Cells - Li, Yu-Liang; Weng, Hao-Cheng; Hsu, Jui-Ling; Lin, Shu-Wha; Guh, Jih-Hwa; Hsu, Lih-Ching (Frontiers in Pharmacology, 2019)
Breast cancer is the most commonly diagnosed cancer and the second leading cause of cancer death in women. Hormone receptor-positive breast cancer is usually subjected to hormone therapy, while triple-negative breast cancer is more formidable and poses a therapeutic challenge. Glucose transporters are potential targets for the development of anticancer drugs. In search of anticancer agents whose effect could be enhanced by a GLUT1 inhibitor WZB117, we found that MK-2206, a potent allosteric Akt inhibitor, when combined with WZB117, showed a synergistic effect on growth inhibition and apoptosis induction in breast cancer cells, including ER(+) MCF-7 cells and triple-negative MDA-MB-231 cells. The combination index values at 50% growth inhibition were 0.45 and 0.21, respectively. Mechanism studies revealed that MK-2206 and WZB117 exert a synergistic cytotoxic effect in both MCF-7 and MDA-MB-231 breast cancer cells by inhibiting Akt phosphorylation and inducing DNA damage. The combination may also compromise DNA damage repair and ultimately lead to apoptosis. Our findings suggest that the combination of Akt inhibitors and GLUT1 inhibitors could be a novel strategy to combat breast cancer.